2020
DOI: 10.1007/s00027-020-0697-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutritional quality and nutrient limitation regimes of phytoplankton in response to declining N deposition in mountain lakes

Abstract: Phytoplankton play a key role in supporting aquatic food webs. However, the effects of ongoing large-scale changes in the concentrations and stoichiometry of important biological compounds [dissolved inorganic N (DIN), total phosphorus (TP), dissolved organic carbon (DOC) and DIN:TP] on the development and nutritional quality of phytoplankton for higher trophic levels are unclear. We conducted lake studies and in situ bioassay experiments in two Swedish mountain regions [Abisko (north) and Jämtland (south)] wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…Methods for FA analysis of seston and zooplankton (or invertebrates) are reported in Bergström et al (2020) and Grieve and Lau (2018 Detailed descriptions of the capillary column and the GC-MS program are given by Bergström et al (2020). Contents of individual FA in seston and zooplankton are reported as mg FA g −1 seston C and mg FA g −1 dry mass, respectively.…”
Section: Fatty Acid Analysis Of Seston and Zooplanktonmentioning
confidence: 99%
“…Methods for FA analysis of seston and zooplankton (or invertebrates) are reported in Bergström et al (2020) and Grieve and Lau (2018 Detailed descriptions of the capillary column and the GC-MS program are given by Bergström et al (2020). Contents of individual FA in seston and zooplankton are reported as mg FA g −1 seston C and mg FA g −1 dry mass, respectively.…”
Section: Fatty Acid Analysis Of Seston and Zooplanktonmentioning
confidence: 99%
“…The relative importance of the two habitats (pelagic and littoral) for consumers is particularly interesting in northern ecosystems, which are experiencing rapid environmental changes, i.e., rising temperatures and precipitation, increasing terrestrial runoff and potential shifts in primary production toward pelagic dominance (Creed et al 2018; Hayden et al 2019). These may have profound effects on lake food webs, especially on the importance and quality of both pelagic and littoral primary producers as well as bacterial contribution to basal resources, available for invertebrate consumers and fish in the higher trophic levels (Ask et al 2009; Creed et al 2018; Hayden et al 2019; Bergström et al 2020).…”
mentioning
confidence: 99%
“…The effect of P-limitation on phytoplankton species composition and food quality for higher trophic levels has been well studied and described (Lukas et al, 2011a, b;Sommer et al, 2012). Bergström et al (2020) analysed N-and P-limitation in two Swedish mountain regions in the context of declining loads of macro-nutrients and found that a proportionally stronger decrease of N (leading to more phases of N-limitation) has a pronounced impact on phytoplankton quality (including as nutrition for higher trophic levels). Elser et al (2009) pointed out that relatively few phytoplankton species have an enhanced ability to capture P, and where excess N shifts waterbodies to P-limitation, these will be favoured, outcompeting others.…”
Section: Co-limitation Of Phytoplankton and Implications For Nutrientmentioning
confidence: 99%